Analysis of Understanding of Ta’awun Principles and Its Influence on the Interest of Online Ojek Drivers to Become Sharia Insurance Participants - Fachrina, Rifka; Marliyah, Marliyah; Syahriza, Rahmi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Online transportation companies have provided insurance facilities for the profession of online motorcycle taxi drivers, but there are still many online motorcycle taxi drivers who do not have self-protection in the form of insurance, even though drivers have a level of work risk that has the potential to endanger their health and safety. The purpose of this research is to find out the online motorcycle taxi drivers' understanding of the ta’awun principle and the online motorcycle taxi drivers’ interest in sharia insurance. This study uses qualitative methods with data collection techniques through interviews. Data processing was carried out using the Miles & Huberman analysis technique which consisted of three stages, namely data reduction, data presentation, and conclusions. Based on data analysis it was concluded that as many as 29% of informants understood the ta’awun principle in sharia insurance. 43% of informants are interested in becoming participants in sharia insurance 67% of them understand the principle of ta’awun while 33% of other people do not understand the principle of ta’awun, 34% of informants are not interested in participating in conventional insurance or sharia insurance as much as 62% of informants admit to knowing the principle of ta’awun awun while 38% of people said they did not understand the principle of ta’awun. 23%, namely 25% of people understand the principle of ta’awun, while 75% of other people do not understand the principle of ta’awun, this percentage explains that the informant is still in doubt about taking Islamic insurance.